The influence of neurotransplantation with different allogenic tissues on the course of the spasticity and chronic pain syndrome after experimental spinal cord injury - Medvediev, Volodymyr V. (Ukrainian Neurosurgical Journal, 2017)
Objective. To examine the effect of neurotransplantation with different allogenic tissue types on the course of the spasticity and chronic pain syndrome after experimental spinal cord injury. Materials and methods. Animals: inbred albino male rats (5.5 months old,300 g); experimental groups: 1 — spinal cord injury + immediate homotopical transplantation of olfactory bulb tissue (TOBT, n = 34); 2 — spinal cord injury + analogous transplantation of fetal (E18) cerebellum tissue (TFСT, n = 15); 3 — spinal cord injury + analogous transplantation of fetal (E18) kidney tissue (TFKT, n = 8); 4 — spinal cord injury only (control group, n = 16). The model of injury was left-side spinal cord hemisection at Т11; spasticity in the ipsilateral hind limb was verified by Ashworth scale. Results. The increase (p < 0.05) of spasticity index was recorded in the control group during the period of 1st — 2nd and 5th month, in TOBT group during the period of 1st — 2nd and 6th month, in TFCT group — during the 3rd week, in TFKT group — during the 2nd week. On the 7th day the spasticity severity in TFCT and TFKT groups was evaluated as 1 point by Ashworth scale, in TOBT and control group it was 0 point. During the 2nd — 4th weeks a high (TFСT, TFKT), intermediate (control group) and low (TOBT) level of spasticity was noticed. The spasticity level in TFСT and TFKT groups exceeded (p < 0.05) the indicator of control group during the 1st — 3rd and 1st — 2nd weeks, respectively. The spasticity level in TOBT group conceded (p < 0.05) to values of the control group (2nd week), TFСT (1st — 6th week) and TFKT (1st — 3rd week). The difference in spasticity values in TFСT and TFKT groups during the experiment was not significant (p > 0.05). On the 24th week of observation the spasticity level in experimental groups was 2.6 ± 0.4 (control group), 2.2 ± 0.2 (TOBT), 2.1 ± 0.3 (TFСT) and 1.9 ± 0.3 (TFKT). Fifty-nine percent of the animals in TOBT group had early spasticity debut with flexion-adduction localization in hip and knee and peripheral paresis (hypotonia/atony) at the ankle joint and high prevalence of severe neurogenic pain manifestation (45 %). Similar spastic localization was noted in 40 % of the animals in TFСT group (for 2nd month) and 25 % of the animals in TFKT group (during 1st — 2nd week). In the control group signs of long-term severe neurogenic pain was found in 19 % animals, in TOBT group — in 27 %, in TFСT group — in 6 % (1 animal), in TFKT group no pain signs observed; the incidence difference was not significant. Conclusion. Approved types of neurotransplantation exert significant influence on the course of spasticity syndrome; the mechanisms of influence related to the cellular structure, angiogenic and immunogenic properties of the grafts.